Answering method of electronic book questions, electronic equipment and computer storage medium - JIANG SHAN; HUANG XINXIA (2018)
The invention discloses an answering method of electronic book questions, electronic equipment and a computer storage medium. The answering method of electronic book questions includes the steps: whendetermining that a received answer request contains an invitation code, acquiring the invitation code contained in the answer request and an identifier of an invited user; determining an identifier,of an invitation user, corresponding to the invitation code, and storing the mapping relation between the identifier of the invited user and the identifier of the invitation user in a preset invitation mapping table; determining whether the answer result of the invited user corresponding to the identifier of the invited user accords with the preset reward rules; and if so, according to the invitation mapping table, determining the identifier, of the invitation user, corresponding to the identifier of the invited user, and sending the invitation reward information to the invitation user corresponding to the identifier o